Jordanian women's use of documentary programs and the fulfilment gained from them (Al-Jazeera Documentary Channels and National Geographic Abu Dhabi as examples) - Qaqish, Odai Ahmad; Al-Momani, Mohammad Hashem (Arab Journal for Sciences and Research Publishing, 2020)
This study focuses on the use of documentaries by Jordanian woman and fulfilled goals achieved through this usage, by conducting a poll for Jordanian women in the three Jordanian regions in order to recognize the effect of these documentaries on Jordanian woman, how important these channels for her and how much she spends watching it.The study focuses on identifying these usages through two channels, Al-Jazeera documentaries and National Geographic Abu Dhabi and it brings the light on the effects of these programs and whether it serves its goals. This study comes to guide the owners of this field to better content and bring these programs to a better level that fulfils the needs of Arabic women and especially Jordanian women. The answers to the study sample which is 300 expose the position of Jordanian women towards documentaries. The results show that 77.3 % of Jordanian women watch documentaries and it fulfils their needs. Also, the results show that 72.4 % of Jordanian women prefer watching National Geographic Abu Dhabi over Al-Jazeera documentaries.
Keywords: Documentary Programs; National Geographic Abu Dhabi; Al Jazeera Documentary; Jordanian Women